A photovoltaic-based SEPIC converter with dual-fuzzy maximum power point tracking for optimal buck and boost operations - Ramalu, Tanaselan; Mohd Radzi, Mohd Amran; Mohd Zainuri, Muhammad Ammirrul Atiqi; Abdul Wahab, Noor Izzri; Abdul Rahman, Ribhan Zafira (MDPI, 2016)
In this paper, a photovoltaic (PV)-based single ended primary-inductor converter (SEPIC) is developed with introduction of dual-fuzzy logic controller (FLC) maximum power point tracking (MPPT) algorithm. Separate FLC parts, for the first time used for MPPT, are configured for optimal operations of both buck and boost operations. During buck operation, a high overshoot voltage exists, and during boost operation, an undershoot voltage occurs, both during the initial rising period. Definitely, a single-FLC MPPT could not be able to minimize both problems, which on the other hand can be handled by the proposed MPPT algorithm. For evaluation purposes, buck operation has been conducted during high irradiance, while during low irradiance, boost operation has been conducted. The dual-FLC MPPT with SEPIC was simulated in MATLAB-Simulink, and further a laboratory prototype was implemented with a TMS320F28335 eZdsp board. Both simulation and experimental results and comparison analysis (with the single-FLC MPPT) have been presented. From the results and analysis, the dual-FLC MPPT performs better than the single-FLC MPPT in terms of faster response time, lower overshoot and undershoot, and further significant reduction of power losses.